Sequential Hybrid Therapy With Pulmonary Endarterectomy and Additional Balloon Pulmonary Angioplasty for Chronic Thromboembolic Pulmonary Hypertension - Yanaka, Kenichi; Nakayama, Kazuhiko; Shinke, Toshiro; Shinkura, Yuto; Taniguchi, Yu; Kinutani, Hiroto; Tamada, Naoki; Onishi, Hiroyuki; Tsuboi, Yasunori; Satomi‐Kobayashi, Seimi; Otake, Hiromasa; Tanaka, Hiroshi; et al. (Journal of the American Heart Association, 2018)
Residual symptoms after pulmonary endarterectomy (PEA) remain as the clinical issues to be solved. Additional balloon pulmonary angioplasty (BPA) after PEA showed its efficacy with symptoms in a case series, although long-term spontaneous recovery of exercise ability after PEA was also reported. However, no studies have validated the clinical efficacy of additional BPA by directly comparing PEA with and without BPA. The aim of this study was to retrospectively evaluate the efficacy of additional BPA as a sequential hybrid therapy for chronic thromboembolic pulmonary hypertension after PEA. Among 44 patients with chronic thromboembolic pulmonary hypertension, 20 patients had residual symptoms after PEA. Of those, 10 patients underwent additional BPA (hybrid group) and were compared with the other 10 patients, who were followed up without BPA (PEA group). The period from PEA to additional BPA was 7.3±2.3 months. In hybrid group, mean pulmonary arterial pressure was significantly improved by PEA (40.6±1.8 to 26.9±3.1 mm Hg, =0.001) and improved further (to 16.7±1.8 mm Hg, =0.002) with additional BPA, which resulted in remarkable improvement in World Health Organization (WHO) functional class (pre- to post-BPA: class I/II/III/IV, 0/5/4/1 to 7/3/0/0; <0.001). Compared with the PEA group at follow-up, the hybrid group achieved better mean pulmonary arterial pressure (18.7±1.7 versus 30.2±3.2 mm Hg, =0.008), WHO functional class (class I/II/III/IV, 7/3/0/0 versus 0/8/2/0; =0.001), and 6-minute walking distance (429±38 versus 319±22 m, =0.028). A sequential hybrid strategy improved residual symptoms and exercise capacity compared with single-PEA therapy.